Preparation of Ag nanoparticles by spark ablation in gas as catalysts for electrocatalytic hydrogen production. Issue 63 (19th October 2020) - Lu, Junda; Guo, Jia; Song, Shihao; Yu, Guangfa; Liu, Hui; Yang, Xiaojing; Lu, Zunming
Abstract : Spark ablation in gas (SAG) technology has the characteristics of being green, fast quenching, fast dynamics and specializes in producing metallic nanoparticles with a clean surface, small size, and abundant defects. Abstract : Spark ablation in gas (SAG) technology has the characteristics of being green, fast quenching, fast dynamics and specializes in producing metallic nanoparticles with a clean surface, small size, and abundant defects. In this study, Ag nanoparticles were prepared via SAG and in situ loaded on a carbon fiber through nitrogen flow. The effect of the carrier gas flow rate and deposition time on the particle size and the dispersibility of the as-prepared Ag nanoparticles on the carbon fiber by SAG were investigated, and the hydrogen evolution reaction (HER) performances of the samples in acidic media were further studied. When the carrier gas flow rate and deposition time are controlled at 5 L min −1 and 120 min, respectively, the sample displays an optimal activity with an overpotential of 362 mV at 10 mA cm −2, which is superior to commercial Ag nanoparticles on carbon fibers. Accordingly, this synthetic technology provides a new way to obtain efficient metallic nano-catalysts and is expected to achieve large-scale application.